Enhancement of side wall growth rate during MOVPE growth on patterned substrates with CCl4 - Kim, MS; Kim, Y; Kim, SI; Hwang, SM; Kang, JM; Park, YK; Min, SK (ELSEVIER SCIENCE SA LAUSANNE, 1995)
With the use of CCl4, which has been utilized as a p-type dopant source for carbon doping of GaAs epilayers during MOVPE growth, very novel growth behaviors of GaAs and AlGaAs layers are observed. It is shown that the CCl4 flow rare is a very important parameter which controls the lateral growth rate on patterned substrates. The ratio of lateral to vertical growth rate of GaAs is increased up to 14 with the CCl4 flow rate. The lateral growth rates of GaAs and AlGaAs can be described as linear functions of CCl4 flow rate. The increase of GaAs lateral growth rate is more remarkable than AlGaAs. This novel characteristic is utilized in fabricating very novel quantum wire structures on V-grooved substrate. Unlike the undoped quantum wire, CCl4-doped quantum wire shows a very large thickness enhancement factor and a unique feature in its shape.
Keywords: LASERS